Challenges faced by people with sickle cell disease in crisis situations: Barriers to emergency (Research, Society and Development, 2021)
Objective: to identify the challenges faced by people with sickle cell disease in the Health Care Network. Method: a descriptive study with a qualitative approach, carried out entirely via text and audio instant messaging with 40 people, through a structured interview asking how much participants' satisfaction with the assistance they received during pain crises. Result: The average age was 18.7 with a prevalence of brown color. It was found that 85% of the public goes to public institutions during pain crises. It was also noticed that few professionals understand sickle cell disease and, therefore, provide low quality care. Conclusion: given the dissatisfaction with the current care model, especially in public institutions, it is necessary to invest in the training of health professionals at different levels of care, so that care is comprehensive and effective.